11 - FMI en Guinée: Un programme très contestable - Alain COURNANEL, (Africa Development, 1985)
In its memoranda of October 29th, 1984, the IMF gave a series of recommandations to Guinea. The main content of these recommandations included drastic measures that had to be taken such as a massive devaluation of the sylis in order to narrow the gap between the official rate and the rate of the black market and to fight against inflation. The fight against inflation would be conducted at the levels of monetary systems and bank ing structure, the financial sector, the public sector and the debt. The main objectives of these measures were to establish the balance of payments and to open up the economy to private capital. The objectives were based on the following hypotheses: (I) inflation and local price rise are imputed to the excess of money supply. This excess and this price rise lead to the de preciation of the exchange rate; (2) on the other hand, there is backlash effect of the foreign exchange on local prices. By setting these objectives in the context of an underdeveloped economy, the IMF totally ignores an important characteristic of inflation in Guinea which is that it is first and foremost structural and not a result of such simple phenoma. In other words, it is triggered by a complex set of factors which emanate from thepolitical and social system as well as existing property relations. Furthermore, the balance between the massive devaluation and the results obtained is unequal because the exchange rate of the black market which is the ultimate goal of the readjustment is not a fixed one. The changing exchange rates cannot guarantee a long lasting balance either. At most, the IMF recommandations can lead to a stagnation of the per capita income by the year 1993. A more severe world crisis would lead to a dramatic decrease of the economic activities and the state will be unable to pay its external debt. Therefore when one considers the analysis of the appropriateness of the proposed program of action, the rather unembar rassed way the IMF proposes the sacking of almost 20.000 agents of the public sector and also the splitting of the state sector, the weakness of the theoretical principles on which this program is based should invite the Guinean Authorities to reject such a strategy.